Dampak Sosial Industri Pertambangan Marmer Didesa Mangilu Kecamatan Bungoro’ Kabupaten Pangkep - Mutiara, Indah Ainun (Universitas Negeri Makassar, 2018)
. The objectives of the study are to examine (i) the social changing process of the people before and after the establishment of marble mining factory, (ii) the social impacts caused by marble mining industry on social life of the people. The study is qualitative research conducted at Mangilu village in Bungoro subdistrict of Pangkajene dan Kepulauan district. The informants were the people at Mangilu village, factory employes, and local government of Mangilu village. File was collected by employing interview, observation, and documentation. File was analyzed by conducting, file reduction, file presentation, and verification or conclusion drawing. The result of the study reveal that the impacts cause by the marble mining factory toward the people of Mangilu village are in positive and negative impacts. The positive impacts can be seen from the education dimension and economy; whereas the negative impacts are in environment and health of the at Mangilu village.